Academic and personal problems among Australian university students who drink at hazardous levels: web‐based survey. (19th December 2013) - Hallett, J.; Howat, P.; McManus, A.; Meng, R.; Maycock, B.; Kypri, K.
Abstract : Issue addressed: Australian university students consume large amounts of alcohol. There is little published information about personal and academic problems associated with this behaviour. We sought to estimate the prevalence, and identify variables associated with, alcohol‐related problems among undergraduate hazardous drinkers. Methods: The control group members (942 undergraduates, 53.3% male, mean age 19.4 years) of an internet‐based intervention trial, who scored !8 on the Alcohol Use Disorders Identification Test, completed two validated questionnaires about their experience of alcohol‐related problems in the preceding 4 weeks. Regression models were used to identify associations between individual characteristics and alcohol‐related problems. Results: One‐quarter of participants had missed a class (25.6%) and/or had been unable to concentrate in class (25.7%), and 45% reported that their drinking had impacted negatively on their learning or grades. The most frequent non‐academic problems were hangovers (74.8%), blackouts (44.8%), emotional outbursts (30.5%), vomiting (28.1%), arguments (20.2%) and drink‐driving (23.2%). Male gender, lower age, being a smoker, being in the Faculty of Health (versus Humanities) and living in shared housing (versus with parents/guardians) were each associated with alcohol‐related problems, whereas year of study had no association. Conclusions: There is a high prevalence of preventable alcohol‐related problems among undergraduates drinking at hazardous levels and a need for restriction of the availability and promotion of alcohol as well as intervention for individuals at high risk. So what?: Universities have a duty of care to large populations of young people drinking at hazardous levels and should make greater efforts to address hazardous alcohol consumption. Abstract : Australian university students consume large amounts of alcohol. There is little published information about personal and academic problems associated with this behaviour. We sought to estimate the prevalence, and identify variables associated with, alcohol‐related problems among undergraduate hazardous drinkers through a web‐based survey. We found a high prevalence of preventable alcohol‐related problems and impacts on academic performance and suggest universities have a duty of care to make greater efforts to address hazardous alcohol consumption.